Neutron powder diffraction study on the iron-based nitride superconductor ThFeAsN. (8th May 2017) - Mao, Huican; Wang, Cao; Maynard-Casely, Helen E.; Huang, Qingzhen; Wang, Zhicheng; Cao, Guanghan; Li, Shiliang; Luo, Huiqian
Abstract: We report neutron diffraction and transport results on the newly discovered superconducting nitride ThFeAsN with . No magnetic transition, but a weak structural distortion around 160 K, is observed by cooling from 300 K to 6 K. Analysis on the resistivity, Hall transport and crystal structure suggests that this material behaves as an electron optimally doped pnictide superconductor due to extra electrons from nitrogen deficiency or oxygen occupancy at the nitrogen site, which, together with the low arsenic height, may enhance the electron itinerancy and reduce the electron correlations, thus suppressing the static magnetic order.